Contribution of Patch Tests with Occupational Handled Products in the Diagnosis of Occupational Contact Dermatitis: A 10-year Review - A. Aloui; M. Maoua; S. El Guedri; A. Moussa; M. Bouhoula; A. Chouchene; I. Kacem; A. Brahem; N. Ghariani; H. Kalboussi; O. El Maalel; S. Chatti; et al. (Dermatology Research and Practice)
Introduction. Allergic contact dermatitis (ACD) is a common occupational disease. Its diagnosis is essentially based on interrogation and patch tests. However, commercially available batteries are sometimes not appropriate for the working conditions and the handled products, which must then be tested. In Tunisia, no previous study has focused on the contribution of patch tests with handled products in the workplace. The objective of this study is to establish the sociodemographic and occupational profile of the patients benefiting from patch tests with handled products in the workplace to identify the characteristics of these products as well as to evaluate the relevance of their positivity and their contributions in terms of aetiological diagnosis of occupational ACD. Methods. This is a retrospective descriptive epidemiological study conducted for a period of 10 years from January 1st, 2006, to December 31, 2015, among patients exercising a professional activity and consulting the Dermato-Allergology Unit of the Occupational Medicine ward of the University Hospital Farhat Hached of Sousse for the exploration of ACD. Results. During the study period, 113 patients received patch tests of handled products in the workplace with a prevalence of 7.3% of patch-tested patients during the same period. The mean age was 35.79 ± 9.45 years with a male predominance (sex ratio = 1.35). The most represented activity sectors were the health sector in 30.1% and the textile sector in 21.2%. The majority of patients were professionally active (61.9% of the study population) with an average professional seniority of 10.28 ± 8.49 months. In total, 138 patch tests with handled products were carried out of which 46 tests were positive (33.3%). After the analytical study, variables independently significantly associated with the positivity of patch tests with handled products in the workplace were the male gender and the working in the plastics industry. An occupational disease was declared to the National Health Insurance Fund for 8 patients, i.e., 7.1% of cases. Conclusion. Patch tests with handled products in the workplace can provide strong arguments for the professional origin of the ACD.